ANALISIS DAN DISAIN PARKIR BERTINGKAT PADA KAWASAN WISATA CANGGU STUDI KASUS CENTRAL PARK CANGGU - I GUSTI AGUNG GDE SURYADARMAWAN; I KETUT SUDIPTA GIRI; I PUTU BAGUS DEVA ANANTA (GANEC SWARA, 2023)
The increase in tourist visits to Bali, especially Badung Regency, has caused many problems, one of which is the problem of parking. From these problems, researchers plan multi-storey parking to meet vehicle parking needs. object of research at Central Park Canggu, North Kuta. The research method used a field survey and the results showed 1) On Saturday the car accumulation was 78 vehicles, for motorbike accumulation was 78 vehicles and on Sunday the car accumulation was 129 vehicles, for motorbike accumulation was 91 vehicles, 2) On Saturday the car parking index was 123% with a capacity of 63 stalls, then an increase was made to 130 stalls to get a parking index of 60%, a motorcycle parking index of 144% with a capacity of 68 stalls, then an increase was made to 136 stalls to get a parking index of 57%, and on Sunday the car parking index was 204% with a capacity of 63 stalls, then an increase was made to 130 stalls to get a parking index of 99%, a motorcycle parking index of 133% with a capacity of 68 stalls, then an increase was made to 136 stalls to get a parking index of 66%.